2007
DOI: 10.1111/j.1600-0846.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive monitoring of oxidative skin stress by ultraweak photon emission measurement. II: biological validation on ultraviolet A‐stressed skin

Abstract: Our data indicate that UVA irradiation induces UPE especially in deeper (living) skin layers, where antioxidants must be active in order to interfere with accelerated skin ageing. Based on the clinical data, and with knowledge of modulating external variables, UPE measurement following UV excitation can be qualified as a reliable and valid method for the non-invasive measurement of antioxidant efficacy on the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…28 In contrast, it has previously been demonstrated that spontaneous ultraweak photon emission is in the bluegreen region of the spectrum. [30][31][32][33] Employing immunoblotting techniques, it has recently been demonstrated that exposure of human skin to UV radiation results in the formation of C ¼ O in the human stratum corneum. 7,25 It was observed that UV-radiation-induced ultraweak photon emission in the human skin showed a maximum of photon emission in the spectral range 400 to 580 nm, supporting the assumption that 3 ðC ¼ OÞ Ã is a main source of ultraweak photon emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In contrast, it has previously been demonstrated that spontaneous ultraweak photon emission is in the bluegreen region of the spectrum. [30][31][32][33] Employing immunoblotting techniques, it has recently been demonstrated that exposure of human skin to UV radiation results in the formation of C ¼ O in the human stratum corneum. 7,25 It was observed that UV-radiation-induced ultraweak photon emission in the human skin showed a maximum of photon emission in the spectral range 400 to 580 nm, supporting the assumption that 3 ðC ¼ OÞ Ã is a main source of ultraweak photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…7,28 In contrast, it has previously been demonstrated that UVAinduced ultraweak photon emission is in the red region of the spectrum. [30][31][32][33] In our present study, we investigated the effect of visible light and UVA radiation on ultraweak photon emission by employing a highly sensitive charge coupled device (CCD) camera and a low-noise photomultiplier tube (PMT). The experimental results show that exposing human skin to UVA radiation enhances ultraweak photon emission, revealing oxidative stress in the human skin.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The ultraweak photon emission or weak chemiluminescence is the most frequent noninvasive technique used for the measurement of oxidative stress because of its direct correlation with the oxidative metabolic processes. [29][30][31][32][33][34][35] The effect of scavengers on ultraweak photon emission was studied in human skin exposed to various types of physical (ultraviolet and ultrasonic radiation) and chemical (hydrogen peroxide, ozone, cigarette smoke) stress factors. [30][31][32][33] It has been demonstrated that topical application of ascorbic acid prior to exposure of human skin to ultraviolet radiation (UV) significantly reduced UV-induced ultraweak photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] The effect of scavengers on ultraweak photon emission was studied in human skin exposed to various types of physical (ultraviolet and ultrasonic radiation) and chemical (hydrogen peroxide, ozone, cigarette smoke) stress factors. [30][31][32][33] It has been demonstrated that topical application of ascorbic acid prior to exposure of human skin to ultraviolet radiation (UV) significantly reduced UV-induced ultraweak photon emission. 33 More recently, a topical application of antioxidant system (tocopheryl acetate, ferulic acid, and rutin) on human skin has been shown to significantly decrease UV-induced ultraweak photon emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation